Pengaruh Pelatihan Teknologi Informasi dan Internship Program terhadap Kualitas SDM pada Mahasiswa Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa dengan Kesiapan Kerja sebagai Variabel Mediasi - Oktavia, Belia Cindy; Kirana, Kusuma Chandra; Syafwan Lysander, Mohammad Ahyar (Universitas Islam Kadiri, 2025)
This study is intended to determine the effect of the Information Technology Training and Internship Program in preparing students' Work Readiness and Human Resources Quality to compete in the world of work in today's digital technology era. The focus and respondents in this study were students of the Faculty of Economics, Sarjanawiyata Tamansiswa University, especially the Class of 2020. The method used in this research process is quantitative method, with research data collection using questionnaires sent via social media to students. The total data collected was 85 data and then processed using a computer with the help of the SPSS version 25 and SmartPLS version 4 applications. The results of the analysis in this study show that variable X1 (Information Technology Training) has a positive and significant effect on variable Y (HR Quality), variable X2 (Internship Program) has a positive and significant effect on variable Y (HR Quality), variable X1 (Information Technology Training) has a positive and significant effect on variable Z (Work Readiness), variable X2 (Internship Program) has a positive and significant effect on variable Z (Work Readiness) and variable Z (Work Readiness) also has a positive and significant effect on variable Y (HR Quality).